The IoT-Based Mathematical Pendulum Real Laboratory Tool - Sudarmanto, Agus; Poernomo, Joko Budi; Maulana, Andika Rifqi (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2023)
Blended learning is a learning approach that combines face-to-face instruction and online learning. In this case, blended learning will be applied to the mathematical pendulum topic through practical experimentation. The mathematical pendulum experiment is a method used to enhance students understanding of the subject matter. This study aims to develop an IoT-based design for a practical mathematical pendulum tool. The research method is based on Research and Development (R&D). The study results in the development of a practical mathematical pendulum tool and control system through the Blynk application. The data displayed on the Blynk application includes the period (t) and the number of oscillations (n). The accuracy of the infrared sensor FC-51 is tested by comparing it with a stopwatch, resulting in a period data accuracy ranging from 96% to 99%. The period data is then used to calculate the acceleration due to gravity (g) with an accuracy ranging from 93% to 97%.